Palladium supported on fluorinated magnesium hydroxide: an efficient catalyst for hydrogenation under ambient conditions - Kokane, Reshma S.; Acham, Vaibhav R.; Kulal, Atul B.; Kemnitz, Erhard; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistryselect, 2017)
In this study palladium supported on fluorinated magnesium hydroxide (Pd-MgF2-x(OH)(x)) was synthesized by fluorination of magnesium hydroxide using aqueous HF as fluorinating agent. The Mg(OH)(2) dissolves in HF and precipitates as magnesium hydroxide fluoride. The Pd precursor was added in the same pot during precipitation of MgF2-x(OH)(x). The final catalyst after drying at 250 degrees C has shown very high efficiency for hydrogenation of styrene and range of nitro aromatics at room temperature and atmospheric pressure. Hydrogenation of styrene has led to 37% conversion with 100% selectivity for hydrogenation of double bond after 3 h. The catalyst was successfully recycled for styrene hydrogenation without appreciable loss in the activity. Further hydrogenation of nitro-aromatics was achieved with 99% conversion and 100% aniline selectivity at room temperature and atmospheric pressure. The turnover number of similar to 21774 was obtained for nitrobenzene hydrogenation. The catalyst has shown mesoporous nature (pore volume 0.25 cc/g, pore diameter 4.8 nm) with very high surface area of 106 m(2)/g. The palladium particle size was found to be in the range of 10-11 nm. Acidity measurements by FTIR of adsorbed pyridine revealed presence of Lewis acidic sites with moderate acidity. Mechanistic studies using in-situ FTIR analysis for nitrobenzene hydrogenation revealed activation of nitrobenzene on the Lewis acid sites of the support whereas activation of hydrogen by heterolytic cleavage on Pd center.